1994
DOI: 10.1055/s-2008-1032453
|View full text |Cite
|
Sign up to set email alerts
|

Chemoembolisation des hepatozellulären Karzinoms: Computertomographische Befunde und klinische Resultate bei prospektiv repetitiver Therapie

Abstract: Between April 1989 and March 1993 162 transarterial chemoembolizations (TACE) were performed repeatedly (mean interval: 2.9 months) in 52 patients with hepatocellular carcinoma (HCC): An emulsion of Lipiodol and epirubicin was injected as selectively as possible in a dosage proportional to liver function and tumour size. Before and after each TACE the size of tumours and ratio of tumour volume containing Lipiodol (RTVCL) were determined in CT and the grade of tumour vascularisation was assessed angiographicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
7

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
0
7
0
7
Order By: Relevance
“…The TACE usually used for the unresectable HCC to lengthen the half-life and increase the average concentration of drug in the tumor, as well as allow more dose-intense delivery in comparison with intravenous administration of chemotherapy (Raoul et al, 1992). These theoretical advantages have made TACE particularly appealing for treatment of HCC patients not amenable to surgical therapy or local ablation (Nakamura et al, 1983;Ikeda et al, 1991;Choi et al, 1992;Bruix et al, 1994;Huppert et al, 1994). Although the TACE has been used since 1983, and there was few studies provide survival benefit of TACE, one study conducted in Barcelona showed the survival probabilities at 1 and 2 years were 82% and 63% for patients who underwent TACE (Llovet et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The TACE usually used for the unresectable HCC to lengthen the half-life and increase the average concentration of drug in the tumor, as well as allow more dose-intense delivery in comparison with intravenous administration of chemotherapy (Raoul et al, 1992). These theoretical advantages have made TACE particularly appealing for treatment of HCC patients not amenable to surgical therapy or local ablation (Nakamura et al, 1983;Ikeda et al, 1991;Choi et al, 1992;Bruix et al, 1994;Huppert et al, 1994). Although the TACE has been used since 1983, and there was few studies provide survival benefit of TACE, one study conducted in Barcelona showed the survival probabilities at 1 and 2 years were 82% and 63% for patients who underwent TACE (Llovet et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Zur Vermeidung kumulativer toxischer Effekte auf das Leberparenchym sind Abstände zwischen mehreren Chemoembolisationen von drei Monaten zu empfehlen. Unter diesen Bedingungen tritt keine progrediente Verschlechterung der Lebersynthesefunktion auf [29,31]. Regelhafte Wiederholungen der TACE ohne Nachweis von Resttumor sind dagegen nicht von Vorteil [32].…”
Section: Patientenunclassified
“…A locally applied chemotherapeutic agent is combined with an application of microspheres and ethiodized oil to occlude tumourous arteries, leading to necrotizing tumour tissue and prolonged drug persistence. 8 Since this treatment targets the tumour blood supply, common evaluation criteria such as the criteria of the response evaluation criteria in solid tumours (RECIST) 9 may not be appropriate to assess the response to treatment. 10 That is due to the commonly recognized limitations of basic concepts of tumour measurement that do not detect early functional response.…”
Section: Introductionmentioning
confidence: 99%